A simple strategy for increasing optical waveguide performance using spherical aberration. (October 2021) - Ferreira, P.H.D.; Almeida, G.F.B.; Mendonça, C.R.
Highlights: Simple strategy to increase waveguide performance using spherical aberration (SA). Fabrication and characterization of waveguides in Eagle glass via fs-laser writing. A trend between microscope objective SA and waveguide losses was obtained. Propagation loss up to 2.5 times smaller with spherical aberrated pulses. Plasma emission was collected, and the different regimes were explained. Abstract: Femtosecond Laser Writing (FLW) has some advantages over competing techniques; it is a direct, highly flexible, and maskless process that can inscribe waveguides in almost any type of transparent material. FLW has proven to produce photonic integrated circuits with innovative design in a deterministic way for several applications, including quantum photonics and microfluidics. Although direct laser writing of waveguides has been extensively studied, there is still an intense search for methods to produce waveguides with lower losses and higher optical quality, because improvements in this sense will impact photonic research and technology. In this work, straight waveguides were directly inscribed into Eagle XG glass samples in a single process step at fabrication depths up to 370 µm. The propagation loss and the mode profile for single-mode waveguides were obtained. The laser pulse energy threshold that triggers the optical breakdown as a function of the depth was measured and used to study its relationship with the resulting waveguide optical properties. A trend between the waveguide losses and the observed pulse energy threshold for optical breakdown was found, which is connected with the microscope objective spherical aberration. It can be useful for finding the best conditions for producing low-loss waveguides. Compared to the waveguides written with the corrected pulses, propagation losses up to 2.5 times smaller were observed in our experiments when applying the strategy presented here. Therefore, by taking advantage of the inherent spherical aberration, the FLW technique can be made capable of much more at even higher intensities than previously possible.